2013
DOI: 10.1097/mao.0b013e3182a1eb83
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intratympanic Steroid Injection, Hyperbaric Oxygen and Combination Therapy in Refractory Sudden Sensorineural Hearing Loss

Abstract: ITS, HBO, and combined therapy offered some benefits in hearing improvement. Combined ITS/HBO may result in a larger WRS improvement and recovery of hearing, especially in lower frequencies. Further randomized prospective studies are needed for confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 32 publications
2
39
1
2
Order By: Relevance
“…Our study showed that HBO therapy as salvage therapy significantly improves the outcome in patients with a hearing loss of >61 dB, while some previous studies have found the benefit of HBO therapy only among patients presenting with profound hearing loss (>80 or >90 dB) [19,21,22] . In the group of patients with a hearing loss of ≤60 dB, improvement was noticed only at low frequencies (0.25 and 0.5 kHz), which is consistent with a previous study on SSNHL that showed that the apical part of the cochlea recover better than the basal parts [24] . Spontaneous recovery of hearing has been described in the first few weeks form the onset of SSNHL, but hearing recovery after the failure of primary therapy is very low.…”
Section: Discussionsupporting
confidence: 78%
“…Our study showed that HBO therapy as salvage therapy significantly improves the outcome in patients with a hearing loss of >61 dB, while some previous studies have found the benefit of HBO therapy only among patients presenting with profound hearing loss (>80 or >90 dB) [19,21,22] . In the group of patients with a hearing loss of ≤60 dB, improvement was noticed only at low frequencies (0.25 and 0.5 kHz), which is consistent with a previous study on SSNHL that showed that the apical part of the cochlea recover better than the basal parts [24] . Spontaneous recovery of hearing has been described in the first few weeks form the onset of SSNHL, but hearing recovery after the failure of primary therapy is very low.…”
Section: Discussionsupporting
confidence: 78%
“…Steroids, vasodilators, plasma expanders, and antiviral and diuretic agents are preferred for these purposes in different combinations [10] . Low-molecular-weight heparin (LMWH) and hyperbaric oxygen (HBO) therapies have also been reported to have some treatment advantages [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to the best of our knowledge, there is very limited data regarding the efficacy of HBO therapy following combined steroid (systemic+ITS) treatment. [10] In our study, we found that the addition of HBO therapy after failure of combined steroid treatment led to statistically significant hearing improvement in patients with severe (≥70 dB) hearing loss. HBO therapy showed significant improvement in mean hearing thresholds at all frequencies.…”
Section: Discussionmentioning
confidence: 71%
“…[12] Although prospective clinical trials of salvage HBO therapy with a control group are limited, result of these studies showed some benefits in hearing improvement. [10,13,14] The results of salvage HBO therapy in previous studies are demonstrated in Table 4. [9,[14][15][16][17][18] To date, no reports have been published about the hearing outcomes of salvage HBO therapy after combined steroid treatment.…”
Section: Discussionmentioning
confidence: 99%